In situ manipulation of the d-band center in metals for catalytic activity in CO oxidation. Issue 27 (9th March 2021) - Lee, Kyung Rok; Yun, Danim; Park, Dae Sung; Yun, Yang Sik; Song, Chyan Kyung; Kim, Younhwa; Park, Jungwon; Yi, Jongheop
Abstract : The d-band center of metal is controlled by using in situ technique without the adding of other materials. Abstract : A combination of in situ XANES, temperature programmed oxidation, kinetic and density functional theory results demonstrate that the d-band centers ( ε d ) of Au and Pt metals are upshifted when 39.9 V m −1 of electric field is applied. This leads to the enhancement of the adsorption strength of CO on both metals, and, thus, results in the promotion (+15%) and the depression (−23%) of CO conversions on Au and Pt, respectively, in the CO oxidation.